DEWAN PERWAKILAN DAERAH (DPD): ANTARA PERWAKILAN DAERAH DAN PERWAKILAN PARTAI POLITIK - Joko J Prihatmoko (Universitas Wahid Hasyim Semarang, 2021)
After the third amendment to the 1945 Constitution, the representative and parliamentary system in Indonesia changed from a unicameral system (one chamber) to a bicameral system (two chambers) consisting of the DPR and DPD. The DPR Chamber is filled with representatives of political parties with ideologies that represent all Indonesian people. While the DPD Chamber is occupied by regional representatives who bridge the territorial representation. Both have an equal position with strong legitimacy through general elections. But in political reality, DPD with limited authority cannot be separated from the influence of political parties. The DPD philosophy as a regional representative institution is challenged by the many interests of political parties in the DPD institution. Keywords: DPD, Regional Representatives, Political Parties